Ketahanan Varietas Padi Toleran Rendaman dan Responnya Terhadap Pemupukan - Ikhwani Ikhwani (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
Ikhwani. 2012. Resistency of Submergence Tolerant Rice Variety and Its Response to Fertilizers. JLSO 2(1):1-13.Submergence Tolerant Rice Varieties (STRV) were needed to anticipate yield reduction due to flash flood. Adoption of good agriculture practices such as nutrient managements for the varieties was expected to reduce yield declaining due to submergence. The objectives of this study were to understand the effects of submergence, fertilizers application and their interaction to plant growth pattern. A pot experiment was conducted in glasshouse at Muara Experimental Farm, Bogor from July to October 2011. The experiment was arranged in a factorial randomized complete block design with three replications. Factor 1 was Fertilizer of 112.5 kg N / ha, in the form of prill urea (P1), SCU / ha (P2), Carbon Coated Urea (CCU) (P3), 400 Ponska kg + 100 kg urea / ha (P4), and treatment1 + 400 kg Silicate fertilizer / ha (P5). Factor 2 was Variety, namely Ciherang sub 1 (V1), Inpara 4 (Swarna sub-1) (V2), Inpara 5 (IR64 sub1) (V3). Total treatments were 15 plus one set of